Double-phase high-temperature damping alloy material and manufacturing method and application thereof

By designing a duplex structure in a high-temperature damping alloy and forming a dense oxide film, the problem of insufficient oxidation resistance of high-temperature damping alloys in the prior art is solved, and high-damping and oxidation resistance in the range of 400-1000℃ is achieved. Suitable for vibration reduction and noise reduction applications in aerospace, transportation and other fields.

CN119121010APending Publication Date: 2024-12-13SHANGHAI UNIV

Patent Information

Application Number
CN202411133207.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing high-temperature damping alloys have insufficient oxidation resistance at above 400℃, which cannot meet the vibration and noise control needs of modern industrial equipment in high-temperature environments.

Method used

A biphasic high-temperature oxidation-resistant damping alloy was designed, with the mass percentage of chemical elements of Cu: 13-17 wt.%, Ni: 8-15 wt.%, Cr: 8-13 wt.%, Fe: 2-6 wt.%, Zn: 3-9 wt.%, Mo: 2-5 wt.%, Al: 0.5-3 wt.%, the balance is Mn and other impurities, forming a structure of fcc and bcc phases, and dense CuO and Cu2O are formed on the surface of the alloy. , mixed oxide films of NiO, Al2O3, and Cr2O3 to improve antioxidant properties.

Benefits of technology

In the high temperature range of 400-1000℃, the alloy has excellent damping and oxidation resistance, and is suitable for vibration noise control in high-temperature oxygen-containing environments. Its oxidation resistance is more than 4 times higher than that of existing MnCu alloys, and it has been extended to use life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121010A_ABST
    Figure CN119121010A_ABST
Patent Text Reader

Abstract

The invention discloses a double-phase high-temperature damping alloy material as well as a manufacturing method and application thereof. The main components of an alloy comprise manganese, copper, nickel, iron, zinc, aluminum and chromium. The preparation method of the high-temperature manganese-based damping alloy material comprises the steps of mother alloy cast ingot preparation, alloy processing and alloy aftertreatment. According to the high-temperature manganese-based damping alloy, the mixing entropy is larger than 1.5 R, and the valence electron concentration is 5.9 < = VEClt; compared with a single-phase fcc structure in the prior art, the high-entropy manganese-based alloy has the advantages that the high-entropy manganese-based alloy is of an fcc and bcc double-phase structure, the interfacial effect caused by double phases can be brought into full play, and the damping performance of the alloy at the high temperature is effectively improved, so that the high-entropy manganese-based alloy has stable high damping performance within the high-temperature range of 400-800 DEG C; the method can be applied to vibration noise control under high-temperature and oxidation environment conditions. The damping alloy is simple in manufacturing process and low in manufacturing cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of metal functional materials, and specifically relates to the design and preparation of a two-phase high-temperature damping alloy. The MnCuNiFeZnAlCrMo high-entropy alloy prepared by the present invention has an applicable temperature range of 400-1000°C and can be widely used in engineering fields such as vibration reduction and noise reduction in aerospace, transportation, engines, etc. Background Art

[0002] High entropy alloys have attracted widespread attention due to their excellent strength, ductility, toughness and good thermal stability. According to the relationship between entropy and system in the Boltzmann hypothesis, for a solid solution alloy containing n elements, its mixing entropy is: Where: R = 8.314 J / (K·mol); c i is the mole fraction of element i, It is generally believed that the entropy value of high entropy alloys is greater than 1.5R, that is, ΔS mix≥1.5R. The high entropy effect of high entropy alloys can effectively inhibit the formation of various ordered intermetallic compound phases in the alloy system, promote the formation of solid solution phases in the alloy system, and make the actual number of phases in the alloy system much lower than the number of phases predicted by the Gibbs phase ratio. The crystal structure of high entropy alloys is generally single phases such as fcc (face-centered cubic), bcc (body-centered cubic), and hcp (hexagonal close-packed). The valence electron concentration VEC often determines the phase type of high entropy alloys. It is generally believed that if VEC <6.87, a single-phase bcc structure tends to be formed; when VEC ≥8, the system is prone to form an fcc phase, and a mixed phase of fcc and bcc is formed when it is between the two. At the same time, the mixing of atoms with different radii often causes a larger lattice distortion, produces a larger solid solution strengthening effect and improves the hardness and strength of the alloy; the phase transformation in high entropy alloys requires the coordinated diffusion of many different atoms to be realized, which will reduce the diffusion rate of atoms in the alloy. This hysteresis diffusion effect helps to form a supersaturated solid solution, increase the recrystallization temperature, reduce the grain growth rate, and increase creep resistance; in addition, the "cocktail" effect of high entropy alloys in performance plays a very important guiding role in the element selection and composition design of high entropy alloys. In view of this, researchers studied the influence of mixing entropy on the mechanical properties of Mn-based damping alloys (Niu Hongkang et al., Materials Guide, 2022, 36(S2):322-327.), and found that the strength and plasticity of this damping alloy with fcc (face-centered cubic) structure increased linearly with the increase of mixing entropy; in the study of high-entropy fcc structure MnCuNiFeZn damping alloy high-temperature damping behavior and phase transition characteristics (Mei Ling et al., Materials Engineering, 2024, 52(01):193-199), the Mn-19%Cu-6%Ni-5%Fe-4%Zn alloy with an entropy value of 1.04R, the internal friction value of the alloy increased sharply above 400°C due to phase transition, and the internal friction value of the alloy increased sharply to 0.092 at 800°C, which makes this alloy have significant industrial application value at high temperatures.

[0003] In the 1960s and 1970s, the British Stone Manganese Marine Company developed the commercially available Sonoston (Mn-37Cu-4Al-3Fe-1.5Ni) cast manganese copper damping alloy. The American International Copper Research Association developed the commercially available Incramute (40Mn-55Cu-Al) deformed manganese copper damping alloy; the high damping characteristic temperature of these alloys is relatively low, resulting in low operating temperatures. At the end of the 20th century, Japan developed the commercially available M2052 (Mn-20Cu-5Ni-2Fe) deformed high manganese damping alloy. The alloy further increases the Mn content, allowing the operating temperature to exceed 80°C, while having high strength and good processing properties. It is an ideal high-strength deformation damping alloy, but its operating temperature is still relatively low and the alloy is easily oxidized. The technology with patent publication number CN114411027A discloses a manganese-copper-based high-strength and high-damping alloy for casting and a preparation method thereof. The chemical composition of the alloy is as follows by weight percentage: Cu: 12.0-14.0%, Ni: 3.0-5.0%, Fe: 1.0-2.0%, Cr: 0.5-0.8%, Al: 0.5-0.8%, Zn: 0.5-0.8%, La: ≤0.01%, C: ≤0.020%, S: ≤0.020%, P: ≤0.010%, Si: ≤0.10%, and the rest is Mn. Its manganese content is not less than 76wt.%, and the alloy is a single-phase fcc austenite structure. Although the damping properties of the alloy are relatively high, the damping properties after aging heat treatment at 400-475℃ are close to 0.035, but only the damping properties of the alloy material at room temperature are disclosed. It is uncertain whether the alloy material can still maintain good material damping properties under high temperature conditions, and it cannot be used at temperatures above 400℃ or higher.

[0004] With the high speed and high power of modern industrial equipment, the existing damping alloys cannot meet the needs of noise and vibration control in certain high temperature environments above 400°C. For this reason, ZL202111078662.7 discloses a high-entropy high-temperature manganese-based damping alloy material and a preparation method thereof, the mass percentage of chemical elements of its component elements is: Cu: 18-23wt.%; Ni: 3-8wt.%; Fe: 1-3wt.%; Zn: 20-25wt.%; the remainder is Mn and other unavoidable impurities. The alloy mixing entropy is not less than 1.18R. This high-entropy manganese-based alloy has high damping performance in the high temperature range of 400°C to 700°C, and can be used for vibration and noise control under complex and high temperature environmental conditions. However, the working environment of high-temperature components is generally very harsh. Not only do they bear certain stresses, but they are also often exposed to oxidative environments. Especially in environments above 700°C, this MnCuNiFeZn damping alloy will be severely oxidized; and alloys with good damping performance at high temperatures, such as Mg-based damping alloys, have not only melted but also been severely oxidized and volatilized, making them completely unusable. For the design and development of high-temperature damping alloys, it is necessary not only to meet the high damping performance at high temperatures, but also to significantly improve the oxidation resistance of the alloy. Summary of the invention

[0005] In order to solve the problem of low oxidation resistance of alloys prepared by the prior art, the purpose of the present invention is to overcome the shortcomings of the existing technology and provide a two-phase high-temperature damping alloy material, a manufacturing method and an application thereof, so that the high-entropy manganese-based alloy of the invention not only has high damping performance in the high temperature range of 600-1000°C, but also has excellent high-temperature oxidation resistance, and can be used for vibration and noise control under high temperature and oxygen-containing environment conditions.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme:

[0007] A high temperature oxidation resistant damping alloy, the mass percentage of chemical elements of its components is:

[0008] Cu: 13-17wt.%;

[0009] Ni: 8-15wt.%;

[0010] Cr: 8-13wt.%;

[0011] Fe: 2-6wt.%;

[0012] Zn: 3-9wt.%;

[0013] Mo: 2-5wt.%;

[0014] Al: 0.5-3wt.%;

[0015] The balance is Mn and other inevitable impurities.

[0016] As a preferred technical solution of the present invention, the mass percentage of chemical elements in the high temperature oxidation resistant damping alloy component is:

[0017] Mn: 45.5-53wt.%;

[0018] Cu: 13-17 wt.%;

[0019] Ni: 8-15wt.%;

[0020] Cr: 8-13wt.%;

[0021] Fe: 2-6wt.%;

[0022] Zn: 3-9wt.%;

[0023] Mo: 2-5wt.%;

[0024] Al: 0.5-3wt.%;

[0025] The balance is other inevitable impurities.

[0026] As a preferred technical solution of the present invention, the phase composition of the high temperature oxidation resistant damping alloy material is fcc phase and bcc phase. The damping alloy of the present invention has ferromagnetic damping caused by the bcc phase and interface damping between the bcc phase and the fcc phase, thereby achieving composite damping enhancement of the material and achieving a comprehensive balance between alloy strength and alloy machinability while ensuring excellent damping properties.

[0027] As a preferred technical solution of the present invention, the high temperature oxidation resistant damping alloy forms a dense mixed main metal oxide film of CuO, Cu2O, NiO, Al2O3, and Cr2O3 on the surface of the alloy matrix to form an oxidation resistant protective surface layer.

[0028] As a preferred technical solution of the present invention, the mixing entropy of the high-temperature oxidation-resistant damping alloy material is greater than 1.5R, and the valence electron concentration is: 5.9≤VEC<6.3.

[0029] As a preferred technical solution of the present invention, the damping performance Q of the high temperature oxidation resistant damping alloy material at a service temperature of 400-800°C is -1 Not less than 0.040.

[0030] A method for preparing the high temperature oxidation resistant damping alloy of the present invention comprises the following steps:

[0031] (1) Preparation of master alloy ingot:

[0032] Putting raw materials with alloy elements in the following mass percentage ratios: Mn: 45.5-53wt.%, Cu: 13-17wt.%, Ni: 8-15wt.%, Cr: 8-13wt.%, Fe: 2-6wt.%, Zn: 3-9wt.%, Mo: 2-5wt.%, Al: 0.5-3wt.% in a crucible, and melting them in a vacuum induction melting furnace, introducing an argon protective atmosphere during the melting period, induction heating to 1400-1600° C. and keeping the temperature for no more than 60 minutes, so that the raw materials are fully melted and then cast, thereby obtaining a master alloy ingot, or casting into an alloy structural part;

[0033] (2) heating the master alloy ingot prepared in step (1) at 900-950° C., and then forging or hot rolling it into an alloy plate, controlling the final rolling or final forging temperature to be not less than 600° C., to obtain an alloy plate;

[0034] (3) The alloy plate prepared in step (2) is subjected to a solution treatment, wherein the solution treatment process comprises maintaining the temperature at 900-950° C. for at least 30 min, and then water quenching to obtain a high-temperature manganese-based damping alloy material.

[0035] As a preferred technical solution of the present invention, in the step (1), during the melting period, induction heating is performed to 1450-1600° C. for heat preservation so that the raw materials are fully melted.

[0036] As a preferred technical solution of the present invention, in the step (1), during the melting period, induction heating is performed for 30-60 minutes to fully melt the raw materials.

[0037] As a preferred technical solution of the present invention, in step (3), the alloy plate prepared in step (2) is placed in a resistance furnace for solution treatment, and the solution treatment time is 30-60 minutes.

[0038] An application of the high temperature oxidation resistant damping alloy of the present invention is to use the high temperature oxidation resistant damping alloy to prepare functional materials and components for vibration reduction, noise reduction and energy absorption, which are used and served under conditions of not less than 400°C.

[0039] As a preferred technical solution of the present invention, the high temperature oxidation resistant damping alloy of the present invention is used and put into service at a temperature not lower than 600°C.

[0040] As a preferred technical solution of the present invention, the applicable temperature range of the high temperature oxidation resistant damping alloy of the present invention is 400-1000°C.

[0041] The design principles of the chemical elements of the induction melting high temperature and high damping manganese-based alloy of the present invention are:

[0042] Mn: has a valence electron number of 7 and is the main element constituting the face-centered cubic fcc phase, i.e., the γ phase crystal lattice. Manganese is very easy to oxidize to form oxides such as MnO, Mn3O4, and Mn2O3, and spinel-type Mn3O4 is very easy to peel off. Since the high-temperature damping performance of the Mn-based alloy originates from the composition of the fcc phase, in order to ensure that the fcc structure in the alloy is the main constituent phase, it is preferred to use a Mn content of 40-60wt.%. When the Mn in the alloy is lower than 40wt.%, the proportion of face-centered cubic fcc phase structure in the alloy is not high enough, the plastic deformation ability of the alloy is reduced, and the pressure processing performance is reduced; when the Mn in the alloy is higher than 60wt.%, the valence electron concentration in the alloy also increases, the proportion of face-centered cubic fcc phase structure is too high, and the strength of the alloy is reduced; in addition, when Mn is higher than 60wt.%, the difficulty of smelting and casting increases, and the process performance of the alloy deteriorates. It is appropriate to use a Mn content of 40-60wt.%; and further preferably 45.5-53wt.%, the performance of the damping alloy is more excellent.

[0043] Cu: The number of valence electrons is 1, which can effectively reduce the concentration of valence electrons in the alloy. In order to stabilize the fcc phase elements, Cu forms an fcc phase solid solution together with Mn, and Cu can form a dense CuO and Cu2O oxide film on the surface of the alloy, providing a certain degree of antioxidant protection and delaying the oxidation process of the alloy in a high temperature environment. When the concentration of Cu is lower than 13wt.%, the Cu content and the Mn content cannot match, and the insufficient Cu content weakens the solid solution strengthening effect of Cu and Mn; when the concentration of Cu is higher than 17wt.%, it is not conducive to improving the strength of the alloy due to the excessively high copper content; therefore, a medium-low copper content of 13-17wt.% is preferably used.

[0044] Ni: The number of valence electrons is 10, which can effectively increase the valence electron concentration in the alloy. In order to stabilize the fcc phase elements, it forms the fcc phase with Mn and is completely dissolved in the fcc lattice, which can enhance the high temperature stability of the alloy. At the same time, Ni can form dense NiO on the surface of the alloy, which is beneficial to improving the oxidation resistance of the alloy. For the dual-phase damping alloy that forms fcc phase and bcc phase, when using medium and low copper content, the Ni content cannot be too low, that is, it cannot be lower than 8wt.%, in order to meet the composition conditions of alloy selection and crystallization, and when the Ni content is higher than 15wt.%, due to the high cost of Ni, the cost of the damping alloy is increased; it is advisable to use a Ni content of 8-15wt.%.

[0045] Fe: The number of valence electrons is 8, which can increase the valence electron concentration in the alloy. It is completely dissolved in the γ phase in the Mn-Cu alloy, which can inhibit the growth of grains and improve the mechanical properties of the material. Since its improvement in oxidation resistance is not obvious, when the Fe content is higher than 6wt.%, the damping performance of the alloy decreases due to excessive Fe content; when the Fe content is lower than 2wt.%, the effect of improving the high-temperature mechanical strength of the damping alloy is not obvious, and the Fe content of 2-6wt.% is preferably used.

[0046] Zn: The number of valence electrons is 2, which can effectively reduce the concentration of valence electrons in the alloy. It is dissolved in Mn, stabilizes the fcc lattice, and can effectively improve the high-temperature damping performance of the alloy. However, Zn has a low melting point and is easily oxidized at high temperatures. When the Zn content is lower than 3wt.%, it cannot improve the damping properties of the damping alloy. When the Zn content is higher than 9wt.%, the difficulty of smelting increases. Considering all factors, it is advisable to use a Zn content of 3-9wt.%.

[0047] Al: The number of valence electrons is 3, which can effectively reduce the valence electron concentration in the alloy and promote the formation of bcc strengthening phase in high entropy alloys. At the same time, a stable Al2O3 oxide film can be formed on the surface of the alloy, which has the excellent performance of blocking oxygen atoms and water molecules, and effectively enhances the oxidation resistance of the alloy. However, when the Al content is higher than 3wt.%, the Al content is too high to affect the melting and casting; when the Al content is lower than 0.5wt.%, the effect of promoting the formation of bcc strengthening phase cannot be achieved. It is advisable to use Al content: 0.5-3wt.%; and further preferably 1-3wt.%, the performance of the damping alloy is more excellent.

[0048] Cr: The number of valence electrons is 6. It promotes the formation of bcc strengthening phase in high entropy alloys, improves the high temperature damping performance of the alloy, and can form a stable Cr2O3 oxide film on the surface of the alloy, effectively enhancing the oxidation resistance of the alloy. Adding Cr is beneficial to improving the corrosion resistance of the alloy. When the Cr content is lower than 8wt.%, the effect on forming the Cr2O3 oxide film and improving the corrosion resistance of the alloy is insufficient. When the Cr content is higher than 13wt.%, its hardness increases and the difficulty of processing and forming increases. It is advisable to use a Cr content of 8-13wt.%.

[0049] Mo: The number of valence electrons is 6. It promotes the formation of bcc strengthening phase in high entropy alloys. When the Mo content is higher than 2wt.%, the high temperature damping performance of the damping alloy can be improved. Mo is easily oxidized and volatilized in high temperature environments, and it is expensive. The Mo content is preferably lower than 5wt.%. Taking all factors into consideration, the Mo content is preferably 2-5wt.%.

[0050] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages:

[0051] 1. The alloy of the present invention contains an fcc matrix phase and a bcc strengthening phase, the mixing entropy of the alloy is greater than 1.5R, and the valence electron concentration is: 5.9≤VEC<6.3, thereby ensuring that the prepared Mn-based alloy has excellent damping performance at 400°C and has continuous high damping performance in a wide temperature range of 400-800°C;

[0052] 2. The present invention can form a dense mixed oxide film of CuO, Cu2O, NiO, Al2O3, and Cr2O3, and form an anti-oxidation protective surface layer on the surface of the alloy matrix. The oxide film of the damping alloy of the present invention is relatively dense. According to the competitive oxidation tendency of different alloying elements in the high entropy alloy, the oxide film formed on the surface of the alloy has the ability to self-repair the oxide film damage during the service of the damping alloy, reducing the chance of exposure of easily oxidized metal atoms. The traditional damping alloy only forms two mixed oxide films of CuO and NiO on the alloy surface, which is not enough to isolate the metal matrix. On this basis, the present invention adopts the formation of more heavy metal main element oxides, which can realize the regeneration compensation of the oxide film in a variety of oxidizing environments, thereby effectively improving the bonding strength between the oxide film and the damping alloy matrix and the continuous integrity of the oxide film. The anti-oxidation performance of the damping alloy of the present invention is more than 4 times higher than that of the existing MnCu alloy, and is more suitable for high-temperature oxidizing environments and has good service stability;

[0053] 3. The alloy of the present invention is a dual-phase high entropy alloy with good castability, can be directly cast into structural parts, has low manufacturing cost, is easy to implement, and is suitable for popularization and application.

[0054] 4. The MnCuNiFeZnAlCrMo high entropy alloy of the present invention has excellent high-temperature damping performance, strong oxidation resistance and corrosion resistance, longer service life, and an applicable temperature range of 400-1000°C. It can be widely used in engineering fields such as vibration reduction and noise reduction in aerospace, transportation, engines, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 It is a comparison chart of the XRD spectra of the high temperature manganese-based damping alloy of Example 1 of the present invention and the damping alloy material of Comparative Example 1.

[0056] Figure 2 This is the surface morphology of the high-temperature manganese-based damping alloy material of Example 1 of the present invention after oxidation at 800° C. for 6 hours.

[0057] Figure 3 This is the surface morphology of the high-temperature manganese-based damping alloy material in Example 1 after oxidation at 800°C for 6 hours. DETAILED DESCRIPTION

[0058] The present invention is further described below in conjunction with the embodiments, and the damping performance is compared with that of the MnCu type manganese-based alloy.

[0059] The damping performance test of the alloys obtained in the embodiment and the comparative example was carried out by a DMA-Q800 dynamic thermomechanical analyzer. The three-point bending mode was used to measure the damping performance (tanδ) and storage modulus (E) of the alloy twins. The test vibration frequency was 1 Hz and the amplitude was 5×10 -5 The oxidation experiment was conducted by using a muffle furnace, with the samples subjected to a high-temperature oxidation test at 600℃~1000℃ and kept warm for 6 hours. In order to avoid experimental errors caused by the shedding of the oxide film, the samples were placed in a crucible and their weights were measured before the experiment. After the experiment, the weights of the samples and crucibles were measured again to study the mass changes of the samples before and after oxidation.

[0060] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:

[0061] Example 1

[0062] In this embodiment, a high-temperature manganese-based damping alloy material is a manganese-based master alloy of Mn-15wt%Cu-10wt%Ni-10wt%Cr-5wt%Fe-6wt%Zn-3wt%Mo-1wt%Al calculated according to the mass percentage of the chemical elements of the component elements. The VEC is 6.06 and the mixing entropy is 1.56R. The preparation method of the high-temperature manganese-based damping alloy material in this embodiment includes the following steps:

[0063] (1) Preparation of master alloy ingot:

[0064] The alloying elements are distributed in the following proportions by weight:

[0065] The raw materials of Mn-15wt%Cu-10wt%Ni-10wt%Cr-5wt%Fe-6wt%Zn-3wt%Mo-1wt%Al are placed in a crucible and melted in a vacuum induction melting furnace. During the melting period, an argon protective atmosphere is introduced, and the raw materials are induction heated to 1450°C and kept warm for 60 minutes, so that the raw materials are fully melted, cast, and solidified to obtain a master alloy ingot;

[0066] (2) heating the master alloy ingot prepared in step (1) at 900° C., and then hot rolling it into an alloy plate with a thickness of 10 mm, controlling the final rolling temperature to be greater than 600° C., to obtain an alloy plate;

[0067] (3) placing the alloy plate prepared in step (2) in a resistance furnace for solution heat treatment, wherein the solution treatment process comprises maintaining the temperature at 950° C. for 30 min, followed by water quenching, to obtain a high-temperature manganese-based damping alloy material.

[0068] The high-entropy high-temperature manganese-based damping alloy material of this embodiment is cut and tested, and it is a fcc and bcc dual-phase structure. Figure 1The internal friction in the temperature range of 400-800℃ is 0.04-0.116; the oxidation weight gain after oxidation at 600-1000℃ for 6h is 4.15-161.69g / m 2 , its oxide film is relatively dense, see attached Figure 2 .

[0069] Example 2

[0070] This embodiment is basically the same as Embodiment 1, except that:

[0071] In this embodiment, a high-temperature manganese-based damping alloy material is a manganese-based master alloy of Mn-13wt%Cu-12wt%Ni-8wt%Cr-3wt%Fe-4wt%Zn-5wt%Mo-2wt%Al calculated according to the mass percentage of the chemical elements of the component elements. The VEC is 6.24 and the mixing entropy is 1.52R. The preparation method of the high-temperature manganese-based damping alloy material in this embodiment includes the following steps:

[0072] (1) Preparation of master alloy ingot:

[0073] The alloying elements are distributed in the following proportions by weight:

[0074] The raw materials of Mn-13wt%Cu-12wt%Ni-8wt%Cr-3wt%Fe-4wt%Zn-5wt%Mo-2wt%Al are placed in a crucible and melted in a vacuum induction melting furnace. During the melting period, an argon protective atmosphere is introduced, and the raw materials are induction heated to 1600°C and kept warm for 60 minutes, so that the raw materials are fully melted, cast, and solidified, thereby obtaining a master alloy ingot;

[0075] (2) heating the master alloy ingot prepared in step (1) at 950° C., and then hot rolling it into an alloy plate with a thickness of 10 mm, controlling the final rolling temperature to be greater than 600° C., to obtain an alloy plate;

[0076] (3) placing the alloy plate prepared in step (2) in a resistance furnace for solution heat treatment, wherein the solution treatment process comprises maintaining the temperature at 900° C. for 30 min, followed by water quenching, to obtain a high-temperature manganese-based damping alloy material.

[0077] The high temperature manganese-based damping alloy material of this embodiment is a dual-phase structure of fcc and bcc. The internal friction of the sample was 0.042-0.105 at 400-800℃; the oxidation weight gain after oxidation at 600-1000℃ for 6h was 4.36-164.51g / m 2 .

[0078] Example 3

[0079] This embodiment is basically the same as the above embodiment, with the following features:

[0080] In this embodiment, a high-temperature manganese-based damping alloy material is a manganese-based master alloy of Mn-14wt%Cu-8wt%Ni-13wt%Cr-6wt%Fe-9wt%Zn-4wt%Mo-0.5wt%Al calculated according to the mass percentage of the chemical elements of the component elements. The VEC is 5.9 and the mixing entropy is 1.62R. The preparation method of the high-temperature manganese-based damping alloy material in this embodiment includes the following steps:

[0081] (1) Preparation of master alloy ingot:

[0082] The alloying elements are distributed in the following proportions by weight:

[0083] The raw materials of Mn-14wt%Cu-8wt%Ni-13wt%Cr-6wt%Fe-9wt%Zn-4wt%Mo-0.5wt%Al are placed in a crucible and melted in a vacuum induction melting furnace. During the melting period, an argon protective atmosphere is introduced and the raw materials are induction heated to 1400°C for 60 minutes to be fully melted, cast, and solidified to obtain a master alloy ingot.

[0084] (2) heating the master alloy ingot prepared in step (1) at 900° C., and then hot rolling it into an alloy plate with a thickness of 10 mm, controlling the final rolling temperature to be greater than 600° C., to obtain an alloy plate;

[0085] (3) placing the alloy plate prepared in step (2) in a resistance furnace for solution heat treatment, wherein the solution treatment process comprises maintaining the temperature at 950° C. for 30 min, followed by water quenching, to obtain a high-temperature manganese-based damping alloy material.

[0086] The high-entropy high-temperature manganese-based damping alloy material of this embodiment is a dual-phase structure of fcc and bcc. The internal friction at 400-800°C is 0.045-0.116; the oxidation weight gain after oxidation at 600-1000°C for 6 hours is 3.94-160.22 g / m 2 .

[0087] Example 4

[0088] This embodiment is basically the same as the above embodiment, with the following features:

[0089] In this embodiment, a high-temperature manganese-based damping alloy material is a manganese-based master alloy of Mn-17wt%Cu-15wt%Ni-12wt%Cr-2wt%Fe-3wt%Zn-2wt%Mo-3wt%Al calculated according to the mass percentage of the chemical elements of the component elements. The VEC is 6.1 and the mixing entropy is 1.59R. The preparation method of the high-temperature manganese-based damping alloy material in this embodiment includes the following steps:

[0090] (1) Preparation of master alloy ingot:

[0091] The alloying elements are distributed in the following proportions by weight:

[0092] The raw materials of Mn-17wt%Cu-15wt%Ni-12wt%Cr-2wt%Fe-3wt%Zn-2wt%Mo-3wt%Al are placed in a crucible and melted in a vacuum induction melting furnace. During the melting period, an argon protective atmosphere is introduced and the raw materials are induction heated to 1500°C for 60 minutes to be fully melted, cast, and solidified to obtain a master alloy ingot.

[0093] (2) heating the master alloy ingot prepared in step (1) at 920° C., and then hot rolling it into an alloy plate with a thickness of 10 mm, controlling the final rolling temperature to be greater than 600° C., to obtain an alloy plate;

[0094] (3) placing the alloy plate prepared in step (2) in a resistance furnace for solution heat treatment, wherein the solution treatment process comprises keeping the temperature at 920° C. for 30 min, and then water quenching to obtain a high-temperature manganese-based damping alloy material.

[0095] The high-entropy high-temperature manganese-based damping alloy material of this embodiment is a dual-phase structure of fcc and bcc. The internal friction at 400-800°C is 0.048-0.121; the oxidation weight gain after oxidation at 600-1000°C for 6 hours is 3.89-158.89 g / m 2 .

[0096] Comparative Example 1

[0097] It is a MnCuNiFeZn damping alloy. A manganese-based alloy with a chemical composition weight percentage of Mn-19wt%Cu-6wt.%Ni-5wt.%Fe-4wt.%Zn was prepared in a vacuum furnace, with a VEC of 6.01 and a mixing entropy of 1.02R. After induction heating at 1350℃ for 60min, it was cast and solidified; the master alloy material was hot-rolled at 900℃ into a 20mm plate, and then solution-treated at 900℃ in a heat treatment furnace for 1 hour and then quenched with water. The alloy has an fcc single-phase structure. Samples were cut for testing. The damping performance of the alloy had an internal friction of 0.013-0.113 at 400-800℃; the oxidation weight gain was 17.25-651.77g / m after oxidation at 600-1000℃ for 6h. 2 The oxide film is extremely loose and partially falls off, see attached Figure 3 .

[0098] Comparative Example 2

[0099] It is a MnCuNiFeZn damping alloy. A manganese-based alloy with a chemical composition weight percentage of Mn-19wt%Cu-5wt.%Ni-2wt.%Fe-22wt.%Zn was prepared in a vacuum furnace, with a VEC of 5.02 and a mixing entropy of 1.21R. After induction heating at 1350℃ for 60min, it was cast and solidified; the master alloy material was hot-rolled at 900℃ into a 20mm plate, and then solution-treated at 900℃ in a heat treatment furnace for 1 hour and then quenched with water. Samples were cut for testing, and the damping performance of the alloy had an internal friction of 0.012-0.098 at 400-800℃; the oxidation weight gain after oxidation at 600-1000℃ for 6h was 21.13-715.61g / m 2 .

[0100] Table 1 is a comparison table of the damping performance and oxidation resistance of the above preferred embodiment alloy and the comparative alloy

[0101]

[0102] It can be seen from Examples 1-4 and Comparative Examples 1-2 that the Mn-based damping alloys prepared by the induction melting method using a manganese-based master alloy containing 45.5-53wt.% Mn, 13-17wt.% Cu, 8-15wt.% Ni, 8-13wt.% Cr, 2-6wt.% Fe, 3-9wt.% Zn, 2-5wt.% Mo, and 0.5-3wt.% Al, all have a fcc and bcc dual-phase structure, as shown in Table 1; at 400°C, the damping performance Q of the high-temperature manganese-based damping alloy of the present invention is -1Not less than 0.04, among which the high temperature damping performance at 400℃ is 4 times that of the existing technology, and its consumption value in the temperature range of 400-800℃ is not lower than that of the existing technology; its antioxidant performance is 4-5 times that of the existing technology, showing stable high damping capacity and excellent antioxidant performance. The high-temperature manganese-based damping alloy materials of the above-mentioned embodiments 1 to 4 can form a dense mixed oxide film of CuO, Cu2O, NiO, Al2O3, and Cr2O3 on the surface of the alloy matrix to form an anti-oxidation protective surface layer. The oxide film formed on the surface of the damping alloy has the ability to self-repair the oxide film damage during the service of the damping alloy, reducing the chance of exposure of easily oxidized metal atoms. The traditional damping alloy only forms two mixed oxide films of CuO and NiO on the alloy surface, which is not enough to isolate the metal matrix. The high-temperature manganese-based damping alloy materials of the above-mentioned embodiments use more abundant metal main element oxides to achieve regeneration compensation of the oxide film in a variety of oxidizing environments, thereby effectively improving the bonding strength of the oxide film with the damping alloy matrix and the continuous integrity of the oxide film. The anti-oxidation performance of the damping alloy of the present invention is more than 4 times higher than that of the existing MnCu alloy, and is more suitable for high-temperature oxidizing environments and has good service stability. The room temperature strength of the high-temperature manganese-based damping alloy material of the above-mentioned embodiment is not less than 570MPa, and the elongation is not less than 20%. The mixing entropy of the damping alloy of the above embodiment is greater than 1.5R, and the valence electron concentration is: 5.9≤VEC<6.3, but the fcc phase and the bcc phase are still formed, so that the damping alloy of the above embodiment has ferromagnetic damping caused by the bcc phase, and has the interface damping between the bcc phase and the fcc phase, realizing the composite damping enhancement of the material, and achieving a comprehensive balance between the alloy strength and the ease of processing of the alloy while ensuring excellent damping characteristics. The damping alloy of the above embodiment alloy complex phase type and alloy matrix has a surface multi-component composite oxide film. The damping alloy of the above embodiment can be used as a functional material that quickly converts and attenuates vibration energy at high temperature, and is used to manufacture parts that need vibration reduction and noise reduction. The vibration reduction efficiency is not less than 90%, which significantly improves the working accuracy of the machine, prolongs the service life, achieves the goal of acoustic stealth of energy absorption, and effectively reduces noise pollution.

[0103] In summary, the high-temperature manganese-based damping alloy of the above embodiment has a mixing entropy greater than 1.5R, a valence electron concentration of 5.9≤VEC<6.3, and both are fcc and bcc dual-phase structures. Compared with the single-phase fcc structure of the prior art, the interface effect caused by the dual phase can be fully utilized to effectively improve the damping performance of the alloy at high temperatures, so that the high-entropy manganese-based alloy of the invention has stable high damping performance in the high temperature range of 400°C to 800°C, and can be used for vibration noise control under high temperature and oxidizing environment conditions of not less than 400°C. The damping alloy of the present invention has a simple manufacturing process and low manufacturing cost.

[0104] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention of the present invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention of the present invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.

Claims

1. A high temperature oxidation resistant damping alloy, characterized in that: The mass percentage of the chemical elements in its components is: Cu: 13-17wt.%; Ni: 8-15wt.%; Cr: 8-13wt.%; Fe: 2-6wt.%; Zn: 3-9wt.%; Mo: 2-5wt.%; Al: 0.5-3wt.%; The balance is Mn and other inevitable impurities.

2. The high temperature oxidation resistant damping alloy according to claim 1, characterized in that: The mass percentages of the chemical elements in its components are: Mn: 45.5-53wt.%; Cu: 13-17 wt.%; Ni: 8-15wt.%; Cr: 8-13wt.%; Fe: 2-6wt.%; Zn: 3-9wt.%; Mo: 2-5wt.%; Al: 0.5-3wt.%; The balance is other inevitable impurities.

3. The high temperature oxidation resistant damping alloy according to claim 1, characterized in that: The phase composition of the alloy material is fcc phase and bcc phase.

4. The high temperature oxidation resistant damping alloy according to claim 1, characterized in that: A dense mixed main metal oxide film of CuO, Cu2O, NiO, Al2O3 and Cr2O3 is formed on the surface of the alloy matrix to form an anti-oxidation protective surface layer.

5. The high temperature oxidation resistant damping alloy according to claim 1, characterized in that: The mixing entropy of the alloy material is greater than 1.5R, and the valence electron concentration is: 5.9≤VEC<6.

3.

6. The high temperature oxidation resistant damping alloy according to claim 1, characterized in that: The damping performance of its alloy material at a service temperature of 400-800℃ is Q -1 Not less than 0.

040.

7. A method for preparing the high temperature oxidation resistant damping alloy according to claim 1, characterized in that: The steps include: (1) Preparation of master alloy ingot: Putting raw materials with alloy elements in the following mass percentage ratios: Mn: 45.5-53wt.%, Cu: 13-17wt.%, Ni: 8-15wt.%, Cr: 8-13wt.%, Fe: 2-6wt.%, Zn: 3-9wt.%, Mo: 2-5wt.%, Al: 0.5-3wt.% in a crucible, and melting them in a vacuum induction melting furnace, introducing an argon protective atmosphere during the melting period, induction heating to 1400-1600° C. and keeping the temperature for no more than 60 minutes, so that the raw materials are fully melted and then cast, thereby obtaining a master alloy ingot, or casting into an alloy structural part; (2) heating the master alloy ingot prepared in step (1) at 900-950° C., and then forging or hot rolling it into an alloy plate, controlling the final rolling or final forging temperature to be not less than 600° C., to obtain an alloy plate; (3) The alloy plate prepared in step (2) is subjected to a solution treatment, wherein the solution treatment process comprises maintaining the temperature at 900-950° C. for at least 30 min, and then water quenching to obtain a high-temperature manganese-based damping alloy material.

8. The method for preparing the high temperature oxidation resistant damping alloy according to claim 7, characterized in that: In the step (1), during the melting period, the material is induction heated to 1450-1600° C. and kept warm so that the raw material is fully melted.

9. An application of the high temperature oxidation resistant damping alloy according to claim 1, characterized in that: The high-temperature oxidation-resistant damping alloy is used to prepare functional materials and components for vibration reduction, noise reduction and energy absorption, and is used and in service at a temperature not lower than 400°C.

10. The use of the high temperature oxidation resistant damping alloy according to claim 9, characterized in that: Use and serve at temperatures not lower than 600°C.

Citation Information

Patent Citations

  • High-entropy high-temperature manganese-based damping alloy material and preparation method thereof

    CN114134378A

  • Manganese-copper-based high-strength and high-damping alloy for casting and preparation method thereof

    CN114411027A

Cited By

  • Thin-wall high-temperature damping alloy pipe fitting as well as preparation method and pouring system thereof

    CN120967211A

  • Iron-containing damping alloy design method and application based on entropy regulation and control

    CN121034483A